Evaluation of physico-mechanical properties of dental plaster modified with pulverized acrylic waste - Ponnapalli, Sai Vishnu; Keerthana, Robbi; Alla, Rama Krishna; Vasavi, Majji; Medicharla, Uma Devi; Ramaraju, AV; Sajjan MC, Suresh (International Journal of Dental Materials, 2023)
Background: Dental plaster is most widely used to make temporary casts and as an investment medium during the fabrication of removable complete and partial denture prostheses. Dental plasters exhibit poor mechanical properties. Aim: This study aimed to evaluate the physico-mechanical properties of dental plaster modified with various concentrations of pulverized acrylic waste. Materials and Methods: A total of 120 specimens were fabricated using dental plaster and were divided into four groups of 30 specimens each to evaluate setting time, one-hour compressive strength, 24-hour compressive strength, and surface reproducibility. Each group was subdivided into five groups of six specimens (n=6), each with the incorporation of various concentrations of pulverized acrylic powder. The specimens incorporated with various concentrations of pulverized acrylic powder (0.5 wt%, 1.0 wt%, 5.0 wt% and 10.0 wt%) were considered as modified groups and the dental plaster with no additives was considered as a control group. The initial and final setting times were measured using a Gillmore needle apparatus, the compressive strength was measured using a universal testing machine, and the surface reproducibility was analyzed using a stereo microscope. The obtained data were subjected to statistical analysis using one-way ANOVA and post hoc analysis. Results: The incorporation of 0.5 wt% resulted in more final and initial setting times. The one-hour and 24-hour compressive strengths of the dental plaster increased with increasing concentration of acrylic waste. Poor surface details were observed with an increase in the concentration of acrylic waste. Conclusions: The addition of acrylic waste resulted in an increase in the one-hour and 24-hour compressive strengths, decreased initial and final setting times, and poor surface reproducibility.